2019
DOI: 10.1016/j.ctro.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Short-course palliative radiation therapy leads to excellent bleeding control: A single centre retrospective study

Abstract: HighlightsHemostatic radiotherapy is highly effective (89% bleeding control).Only 24% of the patients presenting with oncologic bleeding were alive after 1 year.Regimens with >5 fractions are associated with more definitive interruptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 23 publications
1
49
0
Order By: Relevance
“…4,26 Several studies have suggested that shortcourse RT was as efficient as RT administered in a higher number of fractions or long-course RT for obtaining bleeding control. 3,5,6,27 In a previously conducted retrospective study, 20 Gy in 5 fractions (n = 46), 30 Gy in 10 fractions (n = 25), and 8 Gy in a single fraction (n = 21) were the most commonly used regimens in 112 patients who were receiving palliative RT for the control of MH occurring from tumors. 27 Both longer RT regimens (>5 fractions) and shorter regimens (£5 fractions) exerted equal hemostatic effect ( p = 0.497) for an equal duration ( p = 0.652).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,26 Several studies have suggested that shortcourse RT was as efficient as RT administered in a higher number of fractions or long-course RT for obtaining bleeding control. 3,5,6,27 In a previously conducted retrospective study, 20 Gy in 5 fractions (n = 46), 30 Gy in 10 fractions (n = 25), and 8 Gy in a single fraction (n = 21) were the most commonly used regimens in 112 patients who were receiving palliative RT for the control of MH occurring from tumors. 27 Both longer RT regimens (>5 fractions) and shorter regimens (£5 fractions) exerted equal hemostatic effect ( p = 0.497) for an equal duration ( p = 0.652).…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,27 In a previously conducted retrospective study, 20 Gy in 5 fractions (n = 46), 30 Gy in 10 fractions (n = 25), and 8 Gy in a single fraction (n = 21) were the most commonly used regimens in 112 patients who were receiving palliative RT for the control of MH occurring from tumors. 27 Both longer RT regimens (>5 fractions) and shorter regimens (£5 fractions) exerted equal hemostatic effect ( p = 0.497) for an equal duration ( p = 0.652). However, longer regimens caused frequent treatment interruptions and increased hospital days (22.2% vs. 5.3%, p = 0.020).…”
Section: Discussionmentioning
confidence: 99%
“…In the group of patients receiving a BED ≥ 39 Gy 7 out of 17 responded and in the group receiving a BED < 39 Gy 6 out of 7 showed a response (p = NS) [24] . In a recent publication of Sapienza et al , the authors describe the results of a single center study with a large group of patients [18] . In this cohort of 112 patients, bleeding control information was available for 100 patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that palliative radiotherapy (RT) is effective in the management of bleeding, with reported treatment response (i.e. that bleeding would stop or diminish) varying from 45% to 100% [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . It is, however, not clear which RT schedule, with regard to fractionation and total dose, is most ‘optimal’ (with as less fractions and less toxicity for the patient and as much as possible effect on symptom control) to manage bleeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation